Audit Opinion and Profitability on Audit Delay with Company Size as a Moderating Variable - Andriyanto, Andriyanto; Sakti , Bima; Neliana , Tri (Indonesian Journal of Advanced Research, 2024)
With firm size acting as a moderating variable, the aim of this study was to provide empirical evidence of the impact of audit opinion and profitability on audit delay. 25 manufacturing companies in the agricultural sector that were listed on the Indonesia Stock Exchange (IDX) in 2020–2022 served as the study's population. The company's annual financial statements are the source of the data. By using the purposive sampling method, the sampling technique produced 51 samples, or a sample of 17 companies with three years of observation.. Using the SPSS 25 program, this study employs moderation regression analysis and multiple regression analysis techniques with the MRA test approach. The study's findings show that audit opinion has no bearing on audit delay, profitability has no bearing on audit delay, and company size has the ability to considerably mitigate the impact of both profitability and audit opinion on audit delay.ficantly.